Methods of Diagnosing Students' Knowledge of Conducting and Choral Disciplines - Martynenko, Ivan (Professional Art Education, 2020)
Object. The article covers the issues of diagnostics of academic success of students of the Faculty of Arts in conducting and choral disciplines, in particular in the discipline of «Choral Arrangement». Methods. The study used a set of methods: analysis, synthesis, generalization, classification, comparative, prognostic, which highlighted the problems of diagnosing the success of students of arts faculties in conducting and choral disciplines (including choral arrangement), means and forms of its implementation. Results. Diagnostics is an integral part of the educational process. Thanks to it, the quality of achievement of the set purpose is defined. Without diagnostic, it is impossible to effectively manage the didactic process. The need to consider the problems of organization, structure and content of diagnostics is due to the radical changes taking place in the national higher school: introduction into practice of state standards and credit-modular system of organization of educational process. The author defines the concept of «diagnostics» as a system of accurate determination of the results of the didactic process, highlights the main types of control in higher education. The study analyzes the main forms, methods and pedagogical conditions for the quality of the diagnosis of academic success of students of the Art Faculty in conducting and choral disciplines, especially in «Choral Arrangement». Conclusions. The author describes the methods of control as ways by which the effectiveness of educational and cognitive students` activities and teachers` pedagogical work is determined. The study identifies the place of educational creative discipline «Choral Arrangement» in the system of training a professional music teacher of the school, who has practical skills in translating choral, solo, folk works for different choirs, is familiar with the basic theoretical principles, has principles and means of translating musical works for choirs. a certain composition and level of performance.
Keywords: diagnostics; educational achievements; methods of diagnostics; forms and pedagogical conditions of diagnostics; choral arrangement